2011
DOI: 10.1177/0091270010385932
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry Study of Brimonidine Tartrate 0.2% and Apraclonidine 0.5%

Abstract: This study investigated possible effects of brimonidine tartrate 0.2% and apraclonidine 0.5% on pupil diameter. Ten subjects between 20 and 40 years of age participated. A Colvard pupillometer (Oasis Medical) was used to measure pupil diameter. Baseline and serial measurements were obtained at 3 luminance levels (>6.4, <0.82-0.4, and <0.2-0.02 cd/m(2)) during a 4-hour interval following instillation of 1 drop of brimonidine tartrate 0.2% or apraclonidine 0.5% in one eye versus a placebo in the contralateral ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In this study, an average reduction in resting pupil size of 1.78 mm was observed in brimonidine-treated eyes, which is consistent with the results observed in the other studies. 32,36,37 The relationship between log stimulus intensity and pupil contraction amplitude will vary depending on the area of retina being illuminated, in addition to stimulus brightness. The Ganzfeld bowl light stimulus used in this study will undoubtedly produce a greater pupil response than a smaller-sized light stimulus, although scatter of bright light across the retina even with a smaller-sized light tends to recruit larger areas of retina at brighter lights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an average reduction in resting pupil size of 1.78 mm was observed in brimonidine-treated eyes, which is consistent with the results observed in the other studies. 32,36,37 The relationship between log stimulus intensity and pupil contraction amplitude will vary depending on the area of retina being illuminated, in addition to stimulus brightness. The Ganzfeld bowl light stimulus used in this study will undoubtedly produce a greater pupil response than a smaller-sized light stimulus, although scatter of bright light across the retina even with a smaller-sized light tends to recruit larger areas of retina at brighter lights.…”
Section: Discussionmentioning
confidence: 99%
“…Brimonidine exerts most of its pharmacologic effect through a2adrenoreceptor-mediated downregulation of norepinephrine release. [44][45][46][47][48][49][50][51] At present, there is no evidence that the a2 agonist activity of brimonidine exerts a modulatory effect on the iris sphincter and its a1 biological activity has been found to be insignificant. 47 CONCLUSIONS Iris mechanics start to limit the excursion of the pupil, on average, when pupil size reaches 3.3 mm in diameter among subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, less attention is now paid to pupil diameter. Interestingly, among the different glaucoma therapeutics, it has been reported that 0.15 % [21,22] and 0.2 % [23,24] brimonidine has a miotic effect in addition to an intraocular pressure-lowering effect, constricting the pupil from 5-6 to 3-4 mm. It is known that a pupil size of around 3.5 mm is associated with the best visual performance because the effect of aberration and diffraction are the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of concentration when using apraclonidine since the previously mentioned study by Cambron et al 4 demonstrated a miotic effect using apraclonidine 1%. 5 The dissimilar responses of the pupil to 0.5% and 1% apraclonidine could limit the ability of the clinician to appreciate a reversal of the anisocoria in the HS if they are not aware of these differences.…”
Section: Horner Syndromementioning
confidence: 99%